2018
DOI: 10.32474/ciacr.2018.03.000157
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants and Constraints to Small-scale Sheep Marketing in Gombe Metropolis, Gombe State Nigeria

Abstract: The study focused on the socio-economic and challenges faced by small-scale sheep marketers in Gombe metropolis. A multi-stage sampling technique was used to select 91 sheep marketers from four markets. Data were collected using structured questionnaire and were analysed using descriptive statistics, farm budget and multiple regression models. The results revealed that, the mean age of sheep marketers was 40.59 years, 96.70% were males, 86.81% were married, with the majority (87%) had family size ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…A lower ratio indicates an operational efficiency compared to other competing enterprises. This is in line with Saleh et al (2015) who reported that operating ratio is a ratio of an enterprise variable cost to its total revenue. A positive and lower ratio of <1 is desirable as this indicates that in the event of decline in sales or revenue, the firm will maintain its profitability status.…”
Section: Results and Discussion Annual Cost And Returns Analysis Of S...supporting
confidence: 90%
See 1 more Smart Citation
“…A lower ratio indicates an operational efficiency compared to other competing enterprises. This is in line with Saleh et al (2015) who reported that operating ratio is a ratio of an enterprise variable cost to its total revenue. A positive and lower ratio of <1 is desirable as this indicates that in the event of decline in sales or revenue, the firm will maintain its profitability status.…”
Section: Results and Discussion Annual Cost And Returns Analysis Of S...supporting
confidence: 90%
“…This implies that 3.05%of the total revenue goes to pay for the fixed cost of sachet table water enterprises in Gombe central senatorial zone. This agrees with Saleh et al (2015) who viewed that fixed ratio measures enterprise ability to pay for all its fixed charges/expenses with its total revenue. The fixed ratio also viewed as a solvency ratio as it shows how easily an enterprise can pay its bills when they are due.…”
Section: Results and Discussion Annual Cost And Returns Analysis Of S...supporting
confidence: 83%
“…Uncertainty has persisted on how this admirable legislative action have advanced the defense of children's rights. According to studies by Ladan (2017), Ayola (2018), Ashogbon (2018), Saleh and Ibrahim (2019), the domestication of the Child Rights Act in Nigeria have been hampered by a lack of political will. For them, the different state governments avoid taking on the enormous mission of reducing infant mortality by offering top-notch medical care for children as well as expectant and nursing mothers.…”
Section: The Problemmentioning
confidence: 99%
“…This was because large family sizes in the study area tend to realize more outputs than those with few family members. Despite consumption increases with large household; but, cheap family labour was available, investment capacity also improves; thereby enhances the savings behaviour of the households (Saleh, 2016).…”
Section: Age Distribution Of Millet Farmersmentioning
confidence: 99%